2019
DOI: 10.3390/w11040716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sediment Released from a Check Dam on Sediment Deposits and Fish and Macroinvertebrate Communities in a Small Stream

Abstract: Dam removal is typically intended for river restoration or as a countermeasure for aging dams. The influence of dam removal has mainly been studied in large rivers. This study is intended to investigate the influence of the sediment supplied after opening a check dam drain in a small steep stream to contribute to the establishment of sediment release technology form check dam by accumulating the basic knowledge about the influence of sediment release. Deposited sediment in the impoundment was rapidly discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…The Bloede impoundment erosion response was indeed predicted by the two-phase erosion response model developed from observations of the Simkins Dam removal upstream and the Merrimack Village Dam (MVD) in New Hampshire, USA (Collins et al, 2017;Pearson, Snyder, & Collins, 2011). While these two sites had similar dam and watershed sizes, stored sediment quantities and grain size distributions, the two-phase erosion response has also been reported for dam removals across a range of dam and watershed scales in a variety of environmental conditions in the United States, France and Japan (e.g., East et al, 2018;Gilet et al, 2021;Itsukushima et al, 2019;Nagayama et al, 2020). For example, the model well described the erosion response for the Elwha Dam removals, which featured a sediment yield comparable in magnitude to a moderate volcanic eruption like Mount St. Helens in 1980 (East et al, 2018).…”
Section: Impoundment Erosion Quantities and Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bloede impoundment erosion response was indeed predicted by the two-phase erosion response model developed from observations of the Simkins Dam removal upstream and the Merrimack Village Dam (MVD) in New Hampshire, USA (Collins et al, 2017;Pearson, Snyder, & Collins, 2011). While these two sites had similar dam and watershed sizes, stored sediment quantities and grain size distributions, the two-phase erosion response has also been reported for dam removals across a range of dam and watershed scales in a variety of environmental conditions in the United States, France and Japan (e.g., East et al, 2018;Gilet et al, 2021;Itsukushima et al, 2019;Nagayama et al, 2020). For example, the model well described the erosion response for the Elwha Dam removals, which featured a sediment yield comparable in magnitude to a moderate volcanic eruption like Mount St. Helens in 1980 (East et al, 2018).…”
Section: Impoundment Erosion Quantities and Ratesmentioning
confidence: 99%
“…The event-driven phase can last many years depending on a range of factors such as valley morphology, stored sediment caliber and grain size distribution, vegetation feedbacks and event magnitudes and/or frequencies. Pearson, Snyder and Collins (2011) and Collins et al (2017) observed the two-phase erosion response with relatively small, rapidly breached, sand-filled impoundments in the Northeast United States, but it has since been reported for removals of a range of dam sizes and stored sediment quantities in a variety of environmental settings in the United States, France and Japan-including staged removals (Bountry, Lai, & Randle, 2013;Collins et al, 2017;East et al, 2018;Gilet et al, 2021;Itsukushima et al, 2019;Major et al, 2012;Nagayama et al, 2020;Randle et al, 2015). Ferrer-Boix, Martín-Vide & Parker (2014) found similar results in a flume study of staged dam removal: much of the sediment erosion occurred soon after dam removal regardless of flow magnitude.…”
mentioning
confidence: 99%
“…For example, 444 check dams had been constantly constructed in a 200 km 2 catchment (Chabagou catchment) during 1953-1977 to reduce sediment input to the Yellow River and more check dams are planned in this watershed because 60% of them were filled (Fang et al, 2008). Moreover, constructing more and more check dams inevitably reduces the sediment continuity and hydrologic connectivity of a natural catchment (Marchi et al, 2019;Sandercock & Hooke, 2011;Zhao et al, 2020), resulting in multiple consequences such as the sediment starvation of downstream reaches (Galia et al, 2019), disturbance of carbon cycle (Galicia et al, 2019;Liu et al, 2017;Mongil-Manso et al, 2019) and other ecological problems (Itsukushima et al, 2019). Our modelling results implies that ignoring the long-term function of filled check dams may lead to unscientific and uneconomical plan of future check dam construction.…”
Section: Gully Erosion Controlmentioning
confidence: 99%
“…Sediment in river water that is used for drinking can cause human health problems like kidney stones, gallstones, and joint stiffness, and may also cause hardening of the arteries and artery blockage in severe cases (Hussain et al, 2014). Thus, sediment control is among the most important components of water quality management (Kalantari et al, 2018;Hu et al, 2019;Itsukushima et al, 2019). Building dams to control sediment can be cost-effective.…”
Section: Identifying Suitable Sites For Check Dams In Four Scenariosmentioning
confidence: 99%